Manganese contents in fruits and soils in Elazig-Turkey region - Yaman, M; Dilgin, Y; Okumus, N (Chem Soc Pakistan, 2004)
Manganese concentrations in fruit samples were determined by using flame atomic absorption spectrometry (FAAS). To identify the Mn phases most responsible for fruit-available Mn, the soil samples near the fruit plants were also analyzed for Mn by using various digestion and selective extraction reagents. The relation between the fruit-Mn levels and the Mn concentrations in soil extracts was studied. Total Mn concentrations determined in the studied soils and fruits were found in the range of 330 to 1100 and 1.6 to 22 mg/kg, respectively. The negative interferences were observed from Ca, Mg and Al at the higher concentrations than the their concentrations at the measurement step. It was observed that the Mn concentrations of mulberry samples correlate to the manganese concentrations of the cold citric acid extracts of soils.
Keywords: Atomic-Absorption-Spectrometry; Activated Carbon; Speciation; Lead; Enrichment; Cadmium; Nickel; Copper; Iron